A framework of challenges of the transition from E-Government to M-Government in the United Arab Emirates - Alharmoodi, Badir Yousif Ahmed Rafee (2023)
This study aimed to investigate (a) the challenges due to lack of IT infrastructure, (b) the challenges of security and privacy, (c) the challenges associated with IT skills, (d) the knowledge of operating standards and protocols, and (e) the existing operational framework. This study employed a systematic review of previous literature by focusing on the challenges in and opportunities for a successful transition from egovernment to m-government. A survey questionnaire was used to gather the data relating to the study constructs from 250 respondents and the proposed framework was validated by the Fuzzy Delphi method. The survey data were analyzed using Chisquare test that showed the constructs of the study - IT infrastructure, security and privacy, IT skills, knowledge of operating standards and protocols, and operational frameworks - had significant effects on the transition from e-government to mgovernment based on the calculated 2 values not exceeding the threshold value of 9.488 at the level of significance of .05. Therefore, the Fuzzy Delphi method showed there was a strong consensus of opinions among experts regarding the significance of the five constructs and their components, as evidenced by the high percentages of expert agreement ranging from 93% to 100%. These findings will have several implications that the stakeholders need to be aware of the inherent challenges in and opportunities for a successful transition of services from e- government to mgovernment, which can be better understood with the use of the framework developed in this study that highlights the critical parameters involved in such a transition and will enable governments to accomplish efficiency in service delivery to citizens and corporate entities through wireless information and communication as well as integrating various government department and personnel through mobile platforms.